Strategi dan Dampak Implementasi Sekolah Ramah Anak di SDN 1 Kleco - Apri Winge A; Ama Farida Sari (LPPM Universitas 17 Agustus 1945 Semarang, 2025)
This study aims to explore the implementation of Child-Friendly Schools in education at SDN 1 Kleco, focusing on policy aspects, challenges faced, and their impact on the student learning environment. This study uses a qualitative approach with a case study method that involves interviews, observations, and documentation to collect data from school principals, teachers, students, and parents. The results show that although SDN 1 Kleco has implemented the principles of child-friendly schooling, there are still significant challenges, such as limited physical facilities and varying understandings among educators regarding this approach. However, the implementation has positively impacted students' motivation and learning comfort, increasing positive interaction between teachers and students and encouraging better student character development. This research also identifies the importance of parental and community support in strengthening the sustainability of child-friendly school programs. Thus, this research contributes to the development of more inclusive and child-friendly education policies and provides recommendations for improving facilities and more intensive teacher training.